2017
DOI: 10.1111/jdv.14178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adherence predictors for the treatment of moderate to severe psoriasis with biologics: the importance of physician–patient interaction and communication

Abstract: The data reported here underline the importance of patient education and information delivery to optimize patient adherence and thereby treatment outcomes. Treating physicians should be aware that soft aspects of their interaction with the patient might influence treatment adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…34 In patients with acne, the adherence to oral retinoids was 57%, whereas to topical retinoids only 2%. 54 Biologic agents have shown relatively good adherence rates, ranging from 58% to 100%, 52,[58][59][60] which is higher than the adherence rates reported for oral therapy. 61 In two trials including only psoriasis patients, ustekinumab showed the best overall adherence rate among systemic therapies studied (acitretin, methotrexate, adalimumab, etanercept, infliximab).…”
Section: Treatment-relatedmentioning
confidence: 87%
“…34 In patients with acne, the adherence to oral retinoids was 57%, whereas to topical retinoids only 2%. 54 Biologic agents have shown relatively good adherence rates, ranging from 58% to 100%, 52,[58][59][60] which is higher than the adherence rates reported for oral therapy. 61 In two trials including only psoriasis patients, ustekinumab showed the best overall adherence rate among systemic therapies studied (acitretin, methotrexate, adalimumab, etanercept, infliximab).…”
Section: Treatment-relatedmentioning
confidence: 87%
“…Discouraged patients with recalcitrant disease may lose confidence about treatment if they do not observe efficient improvement of their skin symptoms, which can lead to poor medication adherence. 35 Thus, it is important to treat these patients early with rapid-acting biologic therapies, a niche that IL-17 inhibitors fill well.…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion of patients with psoriasis to anti-TNFα therapy is an essential condition for obtaining and maintaining the expected therapeutic outcome, but also a long-term indicator of patient satisfaction. The risk of reactivating the disease in the context of cessation of treatment confers a key role in maintaining the favorable clinical effects to the notion of adherence to therapy (17,18).…”
Section: Discussionmentioning
confidence: 99%